Pembuatan Blok Model Estimasi Sumberdaya Nikel Laterit Dengan Metode Inverse Distance di Wilayah Blok “X” Pada PT. Vale Indonesia Tbk - Burhanudin, Burhanudin; Rauf Husain, Jamal; Bakri, Hasbi (Jurnal of Mining Insight, 2023)
Block model is an attempt to produce estimates of mineral deposition wich is used as a reference for the mining process. The research objective to provide volume and tonnage estimation. The research method using conventional methods Inverse Dictance, needed the data among which the assay data, the data collar, geological data, and survey data. Research carried out by the number of drill point as much as 275 points and a drill spacing of 50 meters and 25 meters generate the amount of resources that have been calculated in the block model in the amount of resources that the limonite layer of 1,210,938 tonnes with the average levels of Ni: 0.8%, Co: 0.08%, Fe: 42.3%, SiO2: 7.8% and MgO: 1.21%. And for saprolite tonnage of 445,090 tonnes with the average levels of Ni: 1.91%,Co:0.18%, Fe: 32.78%, SiO2: 25% and MgO: 7.08%.